2011
DOI: 10.1007/s11434-011-4733-3
|View full text |Cite
|
Sign up to set email alerts
|

Entransy-dissipation-based thermal resistance analysis of heat exchanger networks

Abstract: Heat exchanger network optimization has an important role in high-efficiency energy utilization and energy conservation. The thermal resistance of a heat exchanger network is defined based on its entransy dissipation. In two-stream heat exchanger networks, only heat exchanges between hot and cold fluids are considered. Thermal resistance analysis indicates that the maximum heat transfer rate between two fluids corresponds to the minimum entransy-dissipation-based thermal resistance; i.e. the minimum thermal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Then, Guo et al [11] proposed the extremum entransy dissipation principle for optimizing heat transfer processes where the extremum entransy dissipation corresponds to the optimal heat transfer performance when a thermodynamic cycle is not involved. This new principle has been applied to optimizing heat conduction [11][12][13][14][15][16][17][18][19], convective heat transfer [20][21][22][23], thermal radiation [24] processes and the heat transfer in heat exchanger [25][26][27][28][29][30][31][32][33], with all the studies confirming that the optimal results can be obtained based on the extremum entransy dissipation principle.…”
mentioning
confidence: 74%
“…Then, Guo et al [11] proposed the extremum entransy dissipation principle for optimizing heat transfer processes where the extremum entransy dissipation corresponds to the optimal heat transfer performance when a thermodynamic cycle is not involved. This new principle has been applied to optimizing heat conduction [11][12][13][14][15][16][17][18][19], convective heat transfer [20][21][22][23], thermal radiation [24] processes and the heat transfer in heat exchanger [25][26][27][28][29][30][31][32][33], with all the studies confirming that the optimal results can be obtained based on the extremum entransy dissipation principle.…”
mentioning
confidence: 74%
“…Chen et al [57,58] derived the expressions of equivalent thermal resistance of heat exchanger networks with high and low temperatures based on entansy dissipation. Qian et al [59] investigated three typical heat exchange networks, and found that the thermal resistance is a monotonic function of heat transfer quantity. Cheng et al [60] defined the effectiveness of heat exchanger couple, compared the relationships among entropy generation, entransy dissipation, heat resistance and the effectiveness of heat exchanger couple, and found that only the heat resistance is a monotonic function of the effectiveness of heat exchanger networks.…”
Section: Heat Exchangermentioning
confidence: 99%
“…Examples include the cooling system of electronic devices [1], the thermochemical heat storage system [2], the ground source heat pump system [3], and the thermal control systems of spacecraft [4]. As heat transfer optimization of HE networks can improve heat transport performance and energy utilization, the optimization and analyses of the heat transfer processes in HE networks have received more and more attention [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For two-stream HE networks, Qian et al [5] applied the entransy theory to analyze three typical two-stream HE networks, and found that the minimum EDBTR of the HE networks always corresponds to the maximum heat transfer rates, while the minimum EG does not. For one-stream HE networks, Chen et al [6] optimized the heat transfer in a thermal network with two HEs, and showed that the maximum ED corresponds to the maximum heat transfer rate with prescribed wall temperatures of the HEs, while the minimum EG does not.…”
Section: Introductionmentioning
confidence: 99%